Validitas Lembar Kerja Digital untuk Eksperimen Fisika berbasis Physics Demonstration Videos on YouTube (PDVY) - Rahmadhani Mulvia; Isti Fuji Lestari (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
Science and technology are advancing rapidly, leading to the emergence of the society 5.0 era. In this era, social problem-solving is achieved by integrating physical and virtual spaces through the use of technology. Consequently, there has been a shift in the field of education, where the incorporation of technology is now essential for effective learning. However, traditional teaching methods still prevail due to educators lacking proficiency in utilizing technology. Hence, this study aims to assess the effectiveness of digital worksheets for physics experiments based on Physics Demonstration Videos on YouTube (PDVY). The research methodology employed is the 3D design approach, which involves defining, designing, and developing. The research sample comprises 10 experts in physics education and 12 participants from the science program who are familiar with technology-assisted learning. Data was collected using validation sheets and analyzed quantitatively using the Rasch Model, as well as qualitatively through descriptive analysis. The results indicate that the digital worksheets for physics experiments based on PDVY exhibit good validity, reliability, and varying levels of difficulty. Consequently, this product can be considered suitable for facilitating experimental-based physics learning.